Cost-effectiveness for high dose quadrivalent versus the adjuvanted quadrivalent influenza vaccine in the Italian older adult population - Filippo Rumi; Michele Basile; Americo Cicchetti; Fabián P. Alvarez; Maria Vittoria Azzi; Barbara Muzii (Frontiers in Public Health, 2023)
ObjectivesTo assess the cost-effectiveness of switching from adjuvanted quadrivalent vaccine (aQIV) to high-dose quadrivalent influenza vaccine (HD-QIV) in those aged ≥65 years from the Italian National Health Service perspective.MethodsWe developed a decision tree model over a 1-year time-horizon to assess influenza-related costs and health outcomes. Two hospitalization approaches were considered: “hospitalization conditional on developing influenza” and “hospitalization possibly related to Influenza.” The first approach considered only hospitalizations with influenza ICD-9-CM diagnosis codes. The second included hospitalizations for cardiorespiratory events possibly related to influenza to better capture the “hidden burden”. Since comparative efficacy of high-dose quadrivalent influenza vaccine versus adjuvanted quadrivalent vaccine was lacking, we assumed relative efficacy versus a common comparator, standard-dose influenza quadrivalent vaccines (SD-QIV). We assumed the relative efficacy of HD-QIV vs. SD-QIV was 24.2 and 18.2% for the first and second hospitalization approaches, respectively, based on published information. Due to lack of comparative efficacy data for aQIV vs. SD-QIV, we assumed three different scenarios: 0, 6, and 12% relative efficacy in scenarios 1, 2, and 3, respectively.ResultsFor the first hospitalization approach, HD-QIV was a cost-effective alternative to aQIV in all scenarios at a willingness-to-pay threshold of €30,000 per Quality Adjusted Life Years. The incremental cost-effectiveness ratios across the scenarios were €7,301, €9,805, and €14,733, respectively, much lower than the willingness-to-pay per Quality Adjusted Life Years threshold. For the second hospitalization approach, HD-QIV was a dominant alternative to aQIV across all scenarios. The robustness of the results was confirmed in one-way and probabilistic sensitivity analyses.ConclusionSwitching to HD-QIV from aQIV for the older adult in Italy would improve health-related outcomes, and would be cost-effective or cost saving.